#MeToo meets the mutual fund industry: Productivity effects of sexual harassment - Gjergji Cici; Mario Hendriock; Stefan Jaspersen; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2019)
Sexual harassment, a widespread problem in the workplace, arguably keeps female employees from optimally employing their human capital. We show that removing or diminishing this friction improves productivity. Specifically, using the male-dominated fund industry as our testing ground, we show that productivity of female mutual fund managers significantly increased after the Harvey Weinstein scandal and the onset of the #MeToo movement. Evidence from lawsuits and organizational changes at several fund companies also suggests that reducing the threat of sexual harassment improves productivity. Our results have important implications for the policy debate on workforce diversity and costs of sexual harassment.
Keywords: G23; J21; J71; M50; 330; sexual harassment; mutual fund performance; gender discrimination; organizational frictions; human capital